Nanoencapsulation of ultra-small superparamagnetic particles of iron oxide into human serum albumin nanoparticles - Wacker, Matthias G.; Altinok, Mahmut; Urfels, Stephan; Bauer, Johann (Beilstein Journal of Nanotechnology, 2014)
Human serum albumin nanoparticles have been utilized as drug delivery systems for a variety of medical applications. Since ultra-small superparamagnetic particles of iron oxide (USPIO) are used as contrast agents in magnetic resonance imaging, their encapsulation into the protein matrix enables the synthesis of diagnostic and theranostic agents by surface modification and co-encapsulation of active pharmaceutical ingredients. The present investigation deals with the surface modification and nanoencapsulation of USPIO into an albumin matrix by using ethanolic desolvation. Particles of narrow size distribution and with a defined particle structure have been achieved.
Keywords: diagnostics; HSA; nanoencapsulation; nanoparticles; USPIO